(untitled) (Academic journal Industrial Machine Building Civil Engineering, 2018)
Instrumental inspections and studies experience and results of nine-storeyed residential buildings block-sections actual strained-deformed state under the conditions of their collision in territories of 25 to 35 m thick collapsible soils in Zaporizhzhia city and the subsidence value of 100 cm and more are summarized. It is shown that depending on the process of uneven settlement in the time value of deviation vectors is stabilized over time along with the stabilization of subsidence and deformation of block-section structures on the collision area. It has been established that uneven settlement growth processes stabilization, block-sections deviation from vertical and collision forces is achieved at equilibrium between subsidence values, collision forces of block-sections and resistance of wall sections.